Techno-Economic Feasibility Study Coal Slurry Pipelines Main Report March 1983 - Planning Commission (Planning Commission, 1983)
It would be seen that while share of coal fell from 47.8% to 23.4%, that for oil increased from 39.6% to 47.9%. This was mainly from availability of cheap oil until the energy crisis in 1973. The policy objectives accepted soon after the steep and continuing oil price rise were to step up the development of all available sources of energy with particular emphasis on coal. The latest energy strategy prepared by the Government envisages an integrated system - of conventional as well as of new and renewable energy sources - in which the pride of place has been given to coal.
Planning Commission Government of India
Planning Commission Government of India